FRESHWATER ROTIFER: (PART I) IMPORTANCE, LARVI FOOD, AND CULTURE - Indy, Jeane Rimber; Arías Rodríguez, Lenin; Márquez Couturier, Gabriel; Segers, Hendrik; Álvarez González, Carlos Alfonso; Contreras Sánchez, Wilfrido Miguel (Kuxulkab', 2014)
in finfish larval rearing often depends on the production of phytoplankton as well as zooplankton. Phytoplankton serve as feed for the zooplankton which, in turn, nourish the fish larvae. Different size and types of zooplankton may be raised for different larval stages. Feed production at all stages must be consistent in quality and quantity for the duration of the hatchery cycle if larval rearing is to be successful. We investigated native freshwater rorifer Brachionus angularis, B. quadridentatus brevispinus, and. B. durgae where the last one is reported as a rare an uncommon species in the world which have been collected in Tabasco. The report of freshwater rotifer from Tabasco is divided in two parts, part 1 describes freshwater rotifer from Tabasco, Mexico, as live food, and how to culture them. The second part reports on two species which have been succesfully cultivated in laboratory.